The Influence Of Parents' Authoritary Parenting Styles In Limiting Social Interaction Of Teens In Bah Butong Village - Dahlia Aulia; Siska Astria Br Ginting; Kharisma Nurfaridah; Fara Naia Salsabila; Alfin Siregar (Sean Institute, 2024)
Parenting parent own a very big role in development social and psychological teenagers . One of the pattern frequent foster care implemented by parents is pattern foster authoritarian , which is characterized with strict control , clear rules , and lack of room For discussion . Such as , the attitude and behavior of parents who scold , criticize or give punishment physique at will his heart to his son If his son do mistakes , and parents who always curb child For socialize and choose the people who become Friend children and also parents forbid his son For participate in activity group . The impact caused from parental attitudes and behavior like this , child will own nature and attitude easy offended , scared , not responsible answer , feeling low self , feel No happy , no Can solve the problem is , experiencing difficulty For adapt with environment , especially with his friend or with new people know . The method used in study This is study field is an approach that involves direct data collection from environment or relevant location with Topic study . Research This aiming For know The Influence of Parenting Patterns Authoritarian To Adjustment Social Teenagers in Bah Butong Village . Study This in the background behind the parenting patterns applied by parents to their children in Bah Butong village that is pattern Foster Care Authoritarian Such as , the attitude and behavior of parents who scold and criticize or give punishment physique at will his heart to his son If his son do mistakes , and parents who always curb child For socialize and choose the people who become Friend children and also parents forbid his son For participate in activity group .